Edición y editores catalanes en Buenos Aires : una aproximación a la perspectiva de la gestión editorial a partir de la revista Ressorgiment - Marcela Lucci (Centre de Recherches sur les Mondes Américains, 2016)
In the context of the expansion of the Spanish publishing industry in America during the first half of the 20th century, we track the Catalan presence during the golden age of the publishing industry in Buenos Aires. First, we study the way in which Catalan entrepreneurs were involved in the development of commercial projects in the capital city of the Argentina, Secondly, we briefly discuss the ideological influence of the Ibero-Americanism and Ultramarine separatist catalanism in the Buenos Aires publishing world, during the Spanish Civil War and the first Francoism. Finally, we study the magazine Ressorgiment, as publishing product itself and as a vehicle for the propagation of Catalan publishing projects during Spanish Civil War and the first years of Franco dictatorship.